Evaluating the fitness of human lysozyme transgenic dairy goats: growth and reproductive traits - Jackson, Kathryn A. (Springer Netherlands, 2010)
While there are many reports in the literature describing the attributes of specific applications of transgenic animals for agriculture, there are relatively few studies focusing on the fitness of the transgenic animals themselves. This work was designed to gather information on genetically modified food animals to determine if the presence of a transgene can impact general animal production traits. More specifically, we used a line of transgenic dairy goats expressing human lysozyme in their mammary gland to evaluate the reproductive fitness and growth and development of these animals compared to their non-transgenic counterparts and the impact of consuming a transgenic food product, lysozyme-containing milk. In males, none of the parameters of semen quality, including semen volume and concentration, total sperm per ejaculate, sperm morphology, viability and motility, were significantly different between transgenic bucks and non-transgenic full-sib controls. Likewise, transgenic females of this line did not significantly differ in the reproductive traits of gestation length and litter size compared to their non-transgenic counterparts. To evaluate growth, transgenic and non-transgenic kid goats received colostrum and milk from either transgenic or non-transgenic does from birth until weaning. Neither the presence of the transgene nor the consumption of milk from transgenic animals significantly affected birth weight, weaning weight, overall gain and post-wean gain. These results indicate that the analyzed reproductive and growth traits were not regularly or substantially impacted by the presence or expression of the transgene. The evaluation of these general parameters is an important aspect of defining the safety of applying transgenic technology to animal agriculture.